(3efXhQ cdjs - (3Thbj fGLj(B, (3LhGOs ((3YeGf(B:s (3OGQ GdMGeO(B,s, 2010)
(3EOGQI GdGYeGd aj GdMGVQ , JWhQ GdacQ GdGOGQj , GdcJd GdHjFjI h GdcJd GdYGdejI h GdGOGQI GdCNdGbjGJ h GdeSDhdjI GdELJeGYjI , CSGSjGJ UfY h EJNGP GdbQGQGJ GdEOGQjI , CSGdjH UfGYI h EJNGP GdbQGQ , GdJNWjW GdESJQGJjLj h GdEOGQI , COhGJ GdJNWjW GdESJQGJjLj , CSGSjGJ GdJfXje , JUeje GdJXje , EOGQI GdehGQO GdHTQjI , OjfGejcjI GdbjGOI , GdJMajR GdefXej , GdGJUGd h JHGOd GdeYdheGJ aj GdefXeI , GdLeGYGJ haQb GdYed h GdefGN GdJfXjej , EOGQI GdUQGY h GdELgGO , GdQbGHI GdefXejI , EOGQI JbfjGJ GdeYdheGJ , EOGQI GdYedjGJ , GdJZjjQ GdJfXjej h GdJLOjO , GdQjGOI h GdeTGQjY GdUZjjQI , EOGQI GdUjGfI (B.s
(3eQGLY U(B.541s
Keywords: (3EOGQI GdGYeGds; (3GJNGP GdbQGQs; (3GdGJUGds; (3GdJNWjWs